1997
DOI: 10.1002/(sici)1096-9861(19970818)385:1<43::aid-cne3>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical distribution of vasotocin in a urodele amphibian (Taricha granulosa) revealed by immunohistochemical and in situ hybridization techniques

Abstract: Immunohistochemical and in situ hybridization techniques were used to investigate the neuroanatomical distribution of arginine vasotocin-like systems in the roughskin newt (Taricha granulosa). Vasotocin-like-immunoreactive neuronal cell bodies were identified that, based on topographical position, most likely, are homologous to groups of vasopressin-immunoreactive neuronal cell bodies described in mammals, including those in the bed nucleus of the stria terminalis, medial amygdala, basal septal region, magnoce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 143 publications
(231 reference statements)
0
28
0
Order By: Relevance
“…The anatomical nomenclature as given in Table 2 is based on the studies of Smeets (1992a, 1992b), Lowry et al (1997), Lewis et al (2005), and Hollis et al (2006).…”
Section: Anatomical Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation
“…The anatomical nomenclature as given in Table 2 is based on the studies of Smeets (1992a, 1992b), Lowry et al (1997), Lewis et al (2005), and Hollis et al (2006).…”
Section: Anatomical Nomenclaturementioning
confidence: 99%
“…3k, 5m) of the mesencephalon Table 2 Distribution and relative abundance of three types of AVT receptor mRNAs and immunoreactive cells in the brain and pituitary of the newt (++ intense signal, + moderate signal, -no immunoreactivity or no mRNA hybridization signal). Anatomical nomenclature is according to Smeets (1992a, 1992b), Lowry et al (1997), Lewis et al (2005), and Hollis et al (2006) Structures…”
Section: Avt Receptor Mrna Levels In the Brain And Pituitarymentioning
confidence: 99%
“…The BST of reptiles and amphibians is not differentiated into medial and lateral subdivisions, but a portion of the nucleus contains AVT neurons (Stoll and Voorn, 1985;Smeets et al, 1990;Lowry et al, 1997;Marin et al, 1998), as found for the medial BST of most mammals and birds (De Vries et al, 1985;Caffe et al, 1989;Aste et al, 1998). 3 The POA of fish incorporates peptidergic neuron groups that are homologous to anterior hypothalamic populations in tetrapods (supraoptic and paraventricular nuclei) (Moore and Lowry, 1998).…”
mentioning
confidence: 98%
“…There are VT terminals (Lowry et al 1997) and receptors (Boyd & Moore 1991;Lewis et al 2005) in the newt medulla, although the source of those projections and the circuits through which olfactory stimuli activate them have not yet been identified. Additionally, although we did not characterize individual neuronal responses as did Rose et al (1995), and thus cannot say whether individual neurons are firing more or previously unresponsive neurons are being recruited in response to FSW, our present results are consistent with what they observed when exogenous VT was applied to the medulla, which was that neuronal responses to somatosensory stimuli typically increased.…”
Section: Discussionmentioning
confidence: 99%